Introduction to exercise physiology - Boone, Tommy (Jones & Bartlett Learning, 2014)
Introduction to Exercise Physiology identifies the key scientific content that is critically important to the successful practice of exercise physiology. This text introduces students to the scientific basis for the practice of exercise physiology to prevent or control mind-body diseases, to promote health and well-being, and to enhance athlete performance. The goal of this text is to embrace a new paradigm of exercise physiology as a comprehensive healthcare profession. Introduction to Exercise Physiology emphasizes sound scientific content that will help exercise physiologists design appropriate exercise prescription that focuses on the public health challenges of sedentary living. In addition, the text enables students to understand the effects of sports nutrition and athletic performance by examining exercise metabolism, fuel utilization, and cardiovascular functions and adaptations from a non-performance enhancing supplement perspective. Specific physiologic calculations are presented to teach students how to monitor exercise intensity, as well as to improve the safety and credibility of client-specific test protocols, health and fitness training programs, and athletic competitions. Introduction to Exercise Physiology teaches students the necessary physiologic, electrocardiographic, biomechanic, and anatomic concepts to prepare for and pass the ASEP Board Certification exam. Key Features: Chapters are organized into the following seven major areas in accordance with the emphasis on exercise as medicine: I. Scientific Aspects of Exercise Physiology II. Training the Cardiorespiratory and Muscular Systems III. Training and Performance IV. Exercise Is Medicine V. Exercise Biomechanics VI. Anatomy of Sports and Exercise VII. The Profession of Exercise Physiology Each chapter begins with an overview of the chapter objectives presented in the form of individual questions Chapters conclude by providing students with a list of key terms, a chapter outline, glossary, study questions, suggested readings and references to further student learning Includes a discussion around the importance of exercise physiology as a profession and covers the future challenges for exercise physiologists, the basics of the change process and the importance of a professional organization